Discovering the molecular basis for ligand pharmacological activity on β-adrenoceptors - Bunsuz, Asuman (2023)
G-protein coupled receptors (GPCRs) are the largest and most diverse family of membrane proteins in the human genome and play an important role in cellular signalling by transducing a variety of different external signals to the interior of the cell. Due to their association with numerous human diseases, GPCRs are targeted by almost 34% of approved drugs. Since the discovery of β-blockers by Sir James Black more than 60 years, β-adrenoceptors (βARs) belonging to class A G-protein coupled receptor (GPCR) family have become important therapeutic target for the treatment of cardiovascular and respiratory diseases. Despite success of existing drugs, we still need to better address the needs of patients with both asthma (treated with β2-AR agonists) and cardiovascular dysfunction (treated with β1-AR antagonists), a multi- morbidity combination of conditions that results in two-fold increase in heart failure in asthma patients on medication. This can be achieved by improving sub-type selectivity of drugs, fine-tuning their signalling properties, and increasing their ligand residency times as this would reduce their sensitivity to endogenously secreted adrenalin. Therefore, the identification of the specific and common determinants of ligand pharmacological activity on β1-ARs and β2-ARs and the investigation of the kinetic process of ligand binding to β-adrenergic subtypes are crucial to understand to the molecular mechanism of ligand selectivity between the subtypes. In the first part of this PhD thesis (Chapter 3), we were interested in answering four questions to elucidate the molecular properties of the ligand binding at human β1-ARs and β2-ARs: Can we determine the underlying factors mediating agonism and antagonism for human β1-A at atomic level? Are atomic interactions between ligand and the human β1-AR responsible for their pharmacological properties? Which atomic interactions determine the agonism or antagonism at human β1-ARs? What are the similarities and differences between human β1-ARs and β2-ARs? We aimed to answer these questions by applying molecular docking and machine learning (ML) approaches. In the second part of the thesis (Chapter 4), we focused on the kinetic binding characterization studies at human β1-AR to advance current understanding of the molecular basis for fast or slow ligand binding kinetics. We explored the possible answers to these critical questions for four known β-blockers (Nebivolol, Carvedilol, Bisoprolol and Esmolol): Can we characterize the optimal fluorescent tracer for determination of kinetic binding parameters of unlabelled ligands for human β1-AR? Can we use TR-FRET based approach for the characterization studies for human β1- AR? Can we find the correct ligand binding poses and determine the atomic interactions of these four ligands for human β1-AR? Is there a connection between the atomic interactions and the kinetic binding parameters of these ligands for human β1- AR? By using TR-FRET based approach as alternative to traditional radioligand binding assays, we investigated the ligand binding kinetic for human β1-AR and also revealed the key interactions of the ligands at molecular level via computational experiments.